Non-infectious chronic blepharitis pharmacotherapy - S. N. Sakhnov (Oftalʹmologiâ, 2014)
Purpose: To evaluate the effectiveness of complex treatment included the eyelid hygiene in non-infectious chronic blepharitis patients. Methods: 50 non-infectious chronic blepharitis, meibomian gland dysfunction and dry eye patients (18‑46 years) were examined before and after the treatment (eyelid hygiene using Blepharoshampoo, Blepharolotion or Blepharosalfetka, Blepharogel-1; anti-inflammatory therapy; artificial tears). Traditional ophthalmological examination, consideration of subjective discomfort level, evaluation of meibomian gland function (compression test) and severity of eyelid epitheliopaty (lyssamine green staining), lipid-interferential test, Schirmer’s test, tear film break up time, optical coherent meniscometry, computer evaluation of xerosis indicator (lyssamine green staining) and ocular surface microbiological examination were performed in all the patients. Results: Positive therapeutic effect was noted in all of the observed. It included the following significant changes: reducing the level of subjective discomfort; decreasing of sins of eyelid inflammation; increasing of meibomian gland function; improvement of tear film and ocular surface tissues. Conclusion: Complex treatment, including eyelid hygiene (using Blepharoshampoo, Blepharolotion or Blepharosalfetka, Blepharogel-1), antiinflammatory therapy and artificial tears, allows achieving significant reduction of subjective symptoms and both functional and objective signs of the disease in non-infectious chronic blepharitis patients.